The Day of Atonement : its interpretations in early Jewish and Christian traditions - Hieke, Thomas.; Nicklas, Tobias, 1967- (Themes in Biblical Narrative, 2012)
Established at the center of the Torah, the instructions for the celebration of the "Day of Atonement" hold a prominent position (Leviticus 16). The language of atonement, purification and reconciliation represents the variety of concepts that both explore the complex relationships between God and man, between Yahweh and his chosen people Israel, and that set apart the place of encounter-the sanctuary. Leviticus 16 has served as the point of departure for numerous religious and cultural practices and thoughts that have had a formative influence on Judaism and Christianity up to the present day. The essays in this volume form a representative cross section of the history of the reception of Leviticus 16 and the tradition of the Yom ha-Kippurim.